One Hundred Years of Intuitionism (1907-2007) - van Atten, M. (Springer, 2017)
With logicism and formalism, intuitionism is one of the main foundations for mathematics proposed in the twentieth century; and since the seventies, notably its views on logic have become important also outside foundational studies, with the development of theoretical computer science.